2020
DOI: 10.3390/en13153931
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Analysis of a Diesel Engine during Warm up at Different Coolant and Lubricating Oil Temperatures

Abstract: A comprehensive analysis of combustion behaviour during cold, intermediately cold, warm and hot start stages of a diesel engine are presented. Experiments were conducted at 1500 rpm and 2000 rpm, and the discretisation of engine warm up into stages was facilitated by designing a custom drive cycle. Advanced injection timing, observed during the cold start period, led to longer ignition delay, shorter combustion duration, higher peak pressure and a higher peak apparent heat release rate (AHRR). The peak pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Regulations (EU Directive 2012/46/EU) define cold-start as the first five minutes from the engine start (after the engine has reached thermal equilibrium with the ambient environment) or until the coolant reaches 70 ℃. Within cold-start operation, the engine working condition is not optimal due to the sub-optimal temperature standard of the lubricating oil and engine block, which affect engine performance in addition to the exhaust emissions [9][10][11][12]. Roberts et al [5] reported that an engine cold-start operation consumes more fuel when compared to a warm engine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulations (EU Directive 2012/46/EU) define cold-start as the first five minutes from the engine start (after the engine has reached thermal equilibrium with the ambient environment) or until the coolant reaches 70 ℃. Within cold-start operation, the engine working condition is not optimal due to the sub-optimal temperature standard of the lubricating oil and engine block, which affect engine performance in addition to the exhaust emissions [9][10][11][12]. Roberts et al [5] reported that an engine cold-start operation consumes more fuel when compared to a warm engine.…”
Section: Introductionmentioning
confidence: 99%
“…A cause of inefficiency during cold operation has been attributed to incomplete combustion during the cold-start period due to low fuel and engine temperatures which can lead to higher friction and improper atomisation and evaporation of the fuel [13]. Compared to the hot-start, higher exhaust emissions, fuel consumption, and friction losses, in addition to lower engine power, mechanical efficiency and thermal efficiency during the cold-start period, have been reported in the literature [6,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…These factors lead to higher friction losses, therefore more fuel is needed to maintain the output power. It has been frequently reported that cold-operation leads to higher fuel consumption [31,32] and lower engine power [33,34]. Subsequently, cold-operation leads to higher exhaust emission [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Tests using a commercial 6-cylinder Cummins, Euro III, and turbocharged diesel engine coupled to a dynamometer to evaluate combustion behavior during the cold start, intermediate, and hot operating temperature stages, found that the advanced injection point during the cold start period resulted in a longer ignition delay, shorter combustion duration, maximum combustion chamber pressure, and peak apparent heat release rate of higher combustion than intermediate and hot operating temperature condition (12).…”
mentioning
confidence: 99%